Treatment of COVID-19: Perspective on Convalescent Plasma Transfusion - Farhat, Ryan M.; Mousa, Mohammad A.; Daas, Eshaan J.; Glassberg, Marilyn K. (Frontiers in Medicine, 2020)
The novel coronavirus (COVID-19) has continued its global spread since the first documented case in late 2019 in Wuhan, China. With over 5 million cases and 330 thousand deaths reported worldwide, the need for an effective treatment regimen is evident. Historically, convalescent plasma (CP) has been utilized in the treatment of viral respiratory pathogens. Critically ill patients with COVID-19 in China and South Korea have been treated with CP given the ineffectiveness of experimental therapies with antivirals alone. This commentary explores the importance of published experience and the pending establishment of efficacy to facilitate an informed decision regarding the therapeutic use of CP. With increasing mortality around the world from COVID-19 infection, the need for alternative, effective treatment regimens is critical.